2008
DOI: 10.1016/j.nedt.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the relationship between nursing and health promotion language, theory and practice

Abstract: SummaryThe definitions and meaning qualified nurses employed in an acute NHS hospital setting in the UK gave to health education and health promotion practice and how these fitted established language and theory were investigated qualitatively. These concepts, and the concomitant frameworks and models of practice, have been the subject of considerable debate in the literature. While unresolved both in general and in nursing, a degree of theoretical convergence was established in the 1990s [Bunton, R., Macdonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
1
13
0
12
Order By: Relevance
“…In agreement with previous studies, we observed that despite a positive attitude and awareness of its importance, the definition of HP conveys a more traditional, individual approach and is equated to prevention and health education [24, 41]. This description is not consistent with the tenets of the salutogenic interpretation of the Ottawa Charter, which is based on the values of equity, participation and empowerment [42].…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with previous studies, we observed that despite a positive attitude and awareness of its importance, the definition of HP conveys a more traditional, individual approach and is equated to prevention and health education [24, 41]. This description is not consistent with the tenets of the salutogenic interpretation of the Ottawa Charter, which is based on the values of equity, participation and empowerment [42].…”
Section: Discussionsupporting
confidence: 77%
“…When nurses support people to reflect about their health, life situation and personal resources to find effective coping strategies through solutions, they can act in a health-promoting manner (Antonovsky, 1996). Nurse education has thus an important role in supporting nursing students in creating knowledge for health promotion (Whitehead, 2004) with a broad understanding of how people experience, develop and maintain their health (Piper, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, health education and health promotion are contested concepts. Definitions of health education include improving knowledge and understanding for changes in health‐related behaviour and helping people access health services and manage problems before using them – to notions of empowerment and community development (Piper 2008). True health education activities are voluntary, create understanding, provide skills for rational choices and assist clients in clarifying their values as well as respecting the autonomy of the individual rather than coercing people into adopting expert‐driven ‘medically approved’ behaviours (Whitehead 2009).…”
Section: Mental Health Nursing and Health Promotion In Education Pramentioning
confidence: 99%